STUDI PENDAHULUAN PRODUKSI NITRAT SEBAGAI BAHAN BAKU PUPUK DENGAN METODE PLASMA DISCHARGE - Adi Waskito; Anisya Lisdiana; Herkuswyna Isnaniyah Wahab; Rendra Dwi Firmansyah; Ipin Aripin; Djohar Syamsi; Veny Luvita (Jurnal Penelitian Pertanian Terapan, 2022)
Nitrogen-based fertilizer production mainly involves the Haber-Bosch process, which synthesizes Ammonia via a chemical reaction of N2 from the air and H2 under high temperature and pressure conditions in the presence of a catalyst. However, the environmental concern for greenhouse gas emissions and high energy consumption triggers other Nitrogen fixation method development. The non-thermal plasma oxidation of N2 into Nitrate is a promising method since it has lower energy consumption and a more suitable process condition with a better environmental profile. This study tested the designed plasma discharge reactor tube to produce nitrate from air N2 with varying voltage, time, and airflow rate operating conditions. Nitrate concentration was analyzed using a UV-Vis spectrophotometer. The results show that nitrate concentration changes linearly with the applied voltage in a constant airflow rate and length of treatment time. The highest performance of the plasma discharge reactor was achieved on a 6 kV applied voltage with a flow rate of 0.2 L/min and a treatment time of 40 minutes where the obtained nitrate concentration was 7.7 ppm, which indicated the potential plasma discharged nitrate production for green fertilizer application. Further study shall be carried out to enhance the performance.